Yoga, meditação e silêncio: um estudo na tradição de grandes mestres e na visão científica de Bohdan Wijtenko - Wullstein, Irani Alves Cordeiro (2009)
This thesis focuses the Yoga since its coming from India to the West, with emphasis on the traditional vision that was incorporated by the great masters. It analyses how Yoga has been received in the postmodern society showing matters of wide circulation newspapers and magazines in Brazil. The introductory chapters prepare the scenery for the main focus of the thesis, which aims to recover a remarkable Yogi and Master, Bohdan Wijtenko. During many years, Master Bohdan has been teaching at many universities abroad and in Brazil and has formed a large number of disciples in our society. Although he did not leave books nor articles in scientific newspapers and magazines, many manuscripts and recorded conferences remain unpublished and the thesis tries to recover them, at least partially, in order to show his work as a great scholar of Hinduism and Yoga, and his constant care in teaching meditation and silence as the essence of this millenary practice. In a special way, it shows his pioneer work to deepen the scientific aspects of Yoga, by going trough the meander of the neurosciences